Czy zrównoważony rozwój lokalny jest możliwy? - Zalewski, Alojzy (Is Balanced Local Development Possible?, 2008)
The paper attempts to answer the question of whether it is possible to achieve an equilibrium among nature, economy and society in local development. The analysis shows that accurate prediction of local development impacts and the consequences of their mutual interactions is rather impossible, and the possibility of balancing social, economic and ecological spheres is very limited. For these reasons simultaneous achievement of partial equilibria: socio-economic and ecological, and general socio-economic-ecological equilibrium is not possible. Therefore socio-economic local development should comply with the environmental protection . (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 307-313